Biophysics of Human Hair Structural, Nanomechanical, and Nanotribological Studies - Bhushan, Bharat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents the biophysics of hair. It deals with the structure of hair, its mechanical properties, the nanomechanical characterization, tensile deformation, tribological characterization, the thickness distribution and binding interactions on hair surface. Another important topic of the book is the health of hair, human hair and skin, hair care, cleaning and conditioning treatments and damaging processes. It is the first book on the biophysical properties of hair.
Introduction$1 (BHuman Hair, Skin, and Hair Care Products -- Experimental Methods -- Structural Characterization Using an AFM -- Nanomechanical Characterization Using Nanoindentation, Nanoscratch, and AFM -- Multi-scale Tribological Characterization -- Conditioner Thickness Distribution and Binding Interactions on Hair Surface -- Surface Potential Studies of Human Hair Using Kelvin Probe Microscopy.s
Keywords: Physics; Dermatology; Engineering; Biomedical engineering; Biomaterials; Physics; Biophysics and Biological Physics; Biomaterials; Nanoscale Science and Technology; Biomedical Engineering; Nanotechnology and Microengineering; Dermatology